Главная

Задачник по математике 6 класс Е.А.Бунимович

ГДЗ задачник по математике 6 класс Е.А.Бунимович

авторы: .
издательство: "Просвещение"

Раздел:

Номер №60

Найдите значение выражения:
а)
$\frac{2 - \frac{1}{\frac{1}{2} + \frac{1}{4}}}{2 + \frac{1}{\frac{1}{2} + \frac{1}{4}}}$
;
б)
$\frac{4 + \frac{1}{\frac{1}{2} - \frac{1}{3}}}{4 - \frac{1}{\frac{1}{2} - \frac{1}{3}}}$
;
в)
$1 - \frac{1}{1 + \frac{1}{2}}$
;
г)
$2 + \frac{2}{1 - \frac{2}{3}}$
;
д)
$1 + \frac{1}{1 + \frac{1}{1 + \frac{1}{2}}}$
;
е)
$3 - \frac{3}{3 - \frac{1}{1 - \frac{1}{3}}}$
.

Решение а

$\frac{2 - \frac{1}{\frac{1}{2} + \frac{1}{4}}}{2 + \frac{1}{\frac{1}{2} + \frac{1}{4}}} = \frac{2 - \frac{1}{\frac{2}{4} + \frac{1}{4}}}{2 + \frac{1}{\frac{2}{4} + \frac{1}{4}}} = \frac{2 - \frac{1}{\frac{3}{4}}}{2 + \frac{1}{\frac{3}{4}}} = \frac{2 - \frac{4}{3}}{2 + \frac{4}{3}} = \frac{2 - 1\frac{1}{3}}{2 + 1\frac{1}{3}} = \frac{\frac{2}{3}}{3\frac{1}{3}} = \frac{2}{3} : \frac{10}{3} = \frac{2}{3} * \frac{3}{10} = \frac{1}{1} * \frac{1}{5} = \frac{1}{5}$

Решение б

$\frac{4 + \frac{1}{\frac{1}{2} - \frac{1}{3}}}{4 - \frac{1}{\frac{1}{2} - \frac{1}{3}}} = \frac{4 + \frac{1}{\frac{3}{6} - \frac{2}{6}}}{4 - \frac{1}{\frac{3}{6} - \frac{2}{6}}} = \frac{4 + \frac{1}{\frac{1}{6}}}{4 - \frac{1}{\frac{1}{6}}} = \frac{4 + 6}{4 - 6} = -\frac{10}{2} = -5$

Решение в

$1 - \frac{1}{1 + \frac{1}{2}} = 1 - \frac{1}{1\frac{1}{2}} = 1 - \frac{1}{\frac{3}{2}} = 1 - \frac{2}{3} = \frac{1}{3}$

Решение г

$2 + \frac{2}{1 - \frac{2}{3}} = 2 + \frac{2}{\frac{1}{3}} = 2 + 2 * 3 = 2 + 6 = 8$

Решение д

$1 + \frac{1}{1 + \frac{1}{1 + \frac{1}{2}}} = 1 + \frac{1}{1 + \frac{1}{1\frac{1}{2}}} = 1 + \frac{1}{1 + \frac{1}{\frac{3}{2}}} = 1 + \frac{1}{1 + \frac{2}{3}} = 1 + \frac{1}{1\frac{2}{3}} = 1 + \frac{1}{\frac{5}{3}} = 1 + \frac{3}{5} = 1\frac{3}{5}$

Решение е

$3 - \frac{3}{3 - \frac{1}{1 - \frac{1}{3}}} = 3 - \frac{3}{3 - \frac{1}{\frac{2}{3}}} = 3 - \frac{3}{3 - \frac{3}{2}} = 3 - \frac{3}{3 - 1\frac{1}{2}} = 3 - \frac{3}{1\frac{1}{2}} = 3 - \frac{3}{\frac{3}{2}} = 3 - \frac{3 * 2}{3} = 3 - 2 = 1$